Detection and removal of ceramic clip markers from breast tissue by ultrasound-guided, vacuum-assisted minimally invasive biopsy in a Turkey breast model - Schäfgen, Benedikt; Heil, Jörg; Richter, Hannah; Harcos, Aba; Gomez, Christina; Stieber, Anne; Sohn, Christof; Golatta, Michael (Ultrasound in medicine & biology, 2017)
This article explores the ability of sonographically guided, vacuum-assisted minimally invasive biopsy (VAB) to detect and remove ceramic clip markers from breast tissue. This is a feasibility pre-study for a clinical study using vacuum-assisted biopsy to predict pathologic complete response of breast cancer. Twenty-six ceramic clip markers were placed in five turkey breasts. Clip markers were then detected sonographically and removed using VAB by experienced physicians. Quality of visibility was graded by the performing doctors. The specimens were examined macroscopically to see if they contained the clip marker. The main outcome measure was the accuracy of VAB to detect and remove the clip marker. The VAB device was inspected for any damage possibly caused by hitting the clip marker. The clip markers were detected in 25 cases (96.2%). Twenty clip markers (76.9%) were removed completely by VAB and five (19.2%) were partially removed. One clip marker (3.8%) was not removed. On average, detection of the clip marker took 67 s and the biopsy took 178 s. Quality of visibility was mostly graded as very good (14 cases/53.8%) or good (nine cases/34.6%), and in all of these cases the clip marker was at least partially removed. The clip marker was visible and removed in the vast majority of the cases. VAB is able to remove the clip marker in integrity without causing damage to the system.
Published online: 20 August 2016
Gesehen am 09.04.2018